2017
DOI: 10.1038/s41598-017-09831-9
|View full text |Cite
|
Sign up to set email alerts
|

Routes to probe Bismuth induced strong-coupling superconductivity in bimetallic BiIn alloys

Abstract: We report the observation of strong electron-phonon coupling in intergranular linked BiIn superconductors over an infinite range mediated by low-lying phonons. An enhanced superconducting transition temperature was observed from the magnetization, revealing a main diamagnetic Meissner state below T C (0) = 5.86(1) K and a critical field H C (0) = 1355(15) Oe with an In 2 Bi phase of the composite sample. The electron-phonon coupling to low lying phonons is found to be the leading mechanism for observed strong-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…From the above expression, for a known value of the DOS, high-energy phonons lead to weak EP coupling, 9 whereas low-energy phonons lead to strong EP coupling. 10,11 Takayama et al 1213 discovered a family of ternary platinum phosphide APt 3 P (A = Sr, Ca, and La) SC with T C = 8.4, 6.6, and 1.5 K, respectively. A crossover from weak to strong coupling in InPb bimetallic alloys was observed in our previous work 9 using first-principle calculation and by the Eliashberg theory based on the Allen−Dyne formulation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…From the above expression, for a known value of the DOS, high-energy phonons lead to weak EP coupling, 9 whereas low-energy phonons lead to strong EP coupling. 10,11 Takayama et al 1213 discovered a family of ternary platinum phosphide APt 3 P (A = Sr, Ca, and La) SC with T C = 8.4, 6.6, and 1.5 K, respectively. A crossover from weak to strong coupling in InPb bimetallic alloys was observed in our previous work 9 using first-principle calculation and by the Eliashberg theory based on the Allen−Dyne formulation.…”
Section: Introductionmentioning
confidence: 86%
“…According to the Eliashberg theory based on Allen and Dynes, modified from McMillan formulations, the EP coupling constant can be expressed as , where N ( E F ) gives the density of state (DOS) number at the Fermi level, ⟨ I 2 ⟩ represents Fermi surface average of the squared EP coupling interaction, M is atomic mass, and ⟨ω o 2 ⟩ is an average squared phonon frequency. From the above expression, for a known value of the DOS, high-energy phonons lead to weak EP coupling, whereas low-energy phonons lead to strong EP coupling. , Takayama et al discovered a family of ternary platinum phosphide APt 3 P (A = Sr, Ca, and La) SC with T C = 8.4, 6.6, and 1.5 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, even moderate expansions of the lattice parameter rapidly show dramatic effects on the electron–phonon couplings with λ jumping to a value of 3.5 with a 1% expansion. Such value would represent an absolute record, considerably higher than the highest electron–phonon coupling ever observed in nature (λ = 2.6 in bismuth–lead alloys), and the experimental study of such an extreme regime would be very valuable to understand the limitation of the current theories of superconductivity. Unsurprisingly, for higher strains the system becomes unstable with the emergence of a charge density wave driven by the highly interacting acoustic modes.…”
mentioning
confidence: 97%
“…In previous works, Ag-rich alloyed NPs, such as those containing Au, Cu, or Pt, demonstrated superior bactericidal properties. 4850 Although recent studies have also shown that Bi inhibits some parasitic and microbial growth 5153 and that the addition of Bi could modify the final properties of other alloys, 54,55 to the best of our knowledge, the bactericidal activity of Ag–Bi NAs has not been studied yet.…”
Section: Results and Discussionmentioning
confidence: 99%